COMBINATION THERAPY WITH TARGETED TGF-B INHIBITION FOR TREATMENT OF ADVANCED NON-SMALL CELL LUNG CANCER - VUGMEYSTER Yulia; CHRISTENSEN Olaf; GRENGA Italia; KHANDELWAL Akash; DUSSAULT Isabelle (2021)
This disclosure relates generally to methods for treating a subject diagnosed with advanced non-small-cell lung cancer (NSCLC), involving targeted TGF-Î² inhibition with a bi-functional fusion protein, in combination with administration of systemic chemotherapeutic agents, wherein the combination of the bi-functional fusion protein of the present disclosure with systemic chemotherapeutic agents enhances anticancer efficacy over systemic chemotherapeutic agents alone. Esta descripción se refiere en general a métodos para tratar a un sujeto diagnosticado con cáncer de pulmón de células no pequeñas (NSCLC) avanzado, que implica inhibición de TGF-ß dirigida con una proteína de fusión bifuncional, en combinación con administración de agentes quimioterapéuticos sistémicos, donde la combinación de la proteína de fusión bifuncional de la presente descripción con agentes quimioterapéuticos sistémicos potencia la eficacia contra el cáncer sobre agentes quimioterapéuticos sistémicos solos.